Leaving Coy's Hill : a novel - Sherbrooke, Katherine A. (Pegasus Books, 2021)
Born on a farm in 1818, Lucy Stone dreamed of extraordinary things for a girl of her time, like continuing her education beyond the eighth grade and working for the abolitionist cause, and of ordinary things, such as raising a family of her own. But when she learns that the Constitution affords no rights to married women, she declares that she will never marry and dedicates her life to fighting for change. Based on true events, Leaving Coy's Hill is a timeless story of women's quest for personal and professional fulfillment within society's stubborn constraints. And as an abolitionist and women's rights activist fighting for the future of a deeply divided country, Lucy Stone's quest to live a life on her own terms is as relevant as ever. -- Adapted from publisher's description.